Estrategias socio-afectivas para el desarrollo emocional en los niños de 2 a 3 años de edad del nivel inicial del centro educativo San Juan Bautista de la parroquia San José del cantón Catamayo periodo septiembre 2013-julio 2014 - Jaramillo Romero, Maria Cristina (2015)
This thesis refers to the socio-affective strategies for emotional development in children 2 TO 3 YEARS OF INITIAL school level "SAN JUAN BAUTISTA" SAINT JOSEPH PARISH CANTON CATAMAYO Period September 2013-July 2014 , was aimed at the theoretical analysis of the socio-affective strategies and emotional development in children, the second is based on the diagnosis of the difficulties of emotional development and in turn the implementation of socio-emotional development strategies for improvement emotional. Methods used in the research study were: Analytical Method was used for the study of the theoretical framework it allowed the analysis and critique of concepts and verification of objectives, descriptive method was used to describe the observed reality of the school which allowed developing a project intervention hermeneutical method helped the interpretation of information via books, internet and pdf. Inductive method allowed to know the facts and phenomena when tabulating the results obtained after evaluating the program of socio-affective and emotional development strategies, the statistical method able to analyze the results with a theoretical approach and served to achieving results and analysis both techniques and instruments and evaluation of program activities, Synthetic method served to interpret the information obtained through the application of techniques and instruments in order to reach conclusions and recommendations. Among the techniques an observation guide to children to determine what was the emotional development, teacher A survey was applied to determine what you think about the emotional development in children a test of emotional intelligence (LE Shapiro) aimed at He is allowing parents to know what is the way to educate their children in the emotional aspect. The theoretical framework consists of two variables the first refers to the socio-affective strategies and the second to emotional development. Application of the survey to the teaching we can conclude that although the teaching that does not have enough time to carry out activities with an affective space given; He said that will seek to use the socio-affective strategies to enhance the emotional development of children, and the teacher said it is very important that children have a good emotional development. The application of a test of emotional intelligence LESHAPIRO: a parent we can conclude that they if they assume their mistakes in front of their children, poderles lead in righteousness, they state that a child emotionally this well may pay feasibly in its teaching and learning. The scale of social skills that are applied to children in order to determine how they were in the classroom, if they could fit, socializing with peers, concerning this scale can conclude that some children if they adapted but others do not because they did not like to share with other classmates and their method of defense was aggressive. The conclusions we reached in implementing the program of activities is that the socio-affective and emotional development strategies are very important in the process of growing children because the higher emotions, the better the psicognitivo child development. And one of the recommendations is that the teachers make greater use of recreational activities that enhance sociability in children, otherwise look for innovative strategies that can work with children, with the fixed target have good kids emotionally.